Effects of Post Annealing Treatment on the Characteristics of Ohmic Contacts on n-type AIGaN - Hassan, Z.; Yam, F. K.; Lee, Y. C.; Othman, S. (2005)
In this work, we investigate the thermal stability and surface morphology of Ti metal contact on unintentionally doped n-type aluminum gallium nitride (AIGaN). Different annealing temperatures (400C - 800C) and durations (1-30 minutes) are investigated, as thermally stable metal-semiconductor contacts are essential for high quality devices. Cryogenic quenching after heat treatment is also performed to determine the effects of this treatment on the characteristics of the contacts. Specific contact resistivity, Pc (SCR) determined using transmission line method (TLM) and scanning electron microscopy (SEM) measurements are carried out to be as-deposited, annealed (A), and annealed-and-cryogenically (A=C) treated contacts where the electrical behavior and the surface morphology of eahc of these conditions are compared.